Pengaruh Literasi Digital terhadap Hasil Belajar Mahasiswa Pendidikan Agama Islam di Era Society 5.0 - Dinda Anastasya; Aida Zahwa Qaisara; Raden Muhamad Hilmi Maulana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The educational process, particularly at the higher education level, has been significantly transformed by advances in digital technology. This study aims to analyze the influence of digital literacy on students' learning outcomes in Islamic Religious Education (PAI) courses in the Society 5.0 era. Using a literature review method, the study finds that digital literacy has become an essential competency that helps students access, evaluate, and utilize information effectively to improve their academic performance. Research data were collected from academic publications, scientific journals, and books published between 2017 and 2021. The findings indicate that digital literacy has a positive impact on students' learning outcomes through improved access to learning resources, enhanced critical thinking skills, increased learning motivation, and greater academic participation. However, digital limitations, the spread of unverified information, and the inability to critically evaluate digital religious content remain significant challenges. Therefore, strengthening digital literacy among PAI students is crucial to supporting flexible, critical, and technology-based learning in the Society 5.0 era.